Accommodative Function in Individuals with Autism Spectrum Disorder. Issue 3 (March 2018) - Anketell, Pamela M.; Saunders, Kathryn J.; Gallagher, Stephen M.; Bailey, Clare; Little, Julie-Anne
Abstract : SIGNIFICANCE: Accommodative responses were significantly poorer in individuals with autism spectrum disorder (ASD) compared with age-matched typically developing control subjects, and hypoaccommodation was associated with reduced near visual acuity (NVA) and convergence. PURPOSE: Autism spectrum disorder is a neurodevelopmental disorder with a reported prevalence of 1.1 to 1.5%. Accommodative dysfunction has been noted in other developmental conditions including cerebral palsy and Down syndrome. The aim of this study was to investigate how accommodative accuracy and near visual function in ASD compared with typically developing control subjects. METHODS: This study investigated accommodative function in children with ASD, in conjunction with other vision measures with habitual refractive corrections. Accommodative accuracy was assessed using modified Nott dynamic retinoscopy. Individual accommodative demand and response were calculated incorporating residual refractive error (difference between cycloplegic and habitual refractive state). Near visual measures included NVA, near point of convergence, fusional reserves, and stereoacuity. Cycloplegic autorefraction confirmed refractive error. RESULTS: Accommodative responses were measured from 124 participants with ASD (6 to 17 years old) and 204 age-matched control subjects. There was no significant difference in the magnitude of residual refractive error between groups ( P = .10). The prevalence of a clinically significant lag of accommodation was greater in the ASD group compared with control subjects (ASD = 17.4%, control subjects = 4.9%, χ 2 = 13.04, P < .0001). Near visual acuity was significantly reduced in the ASD group with a clinically significant lag of accommodation ( P < .01). A few participants (n = 24 control subjects, n = 14 ASD) had uncorrected or undercorrected refractive errors (spherical equivalent refractive error ≥+2.00 D, >1.00 DC), and when these were removed from analysis, there was still an increased prevalence of hypoaccommodation in ASD (14.7%). CONCLUSIONS: Children with ASD were significantly more likely to have accommodative deficits (and associated near visual deficits) in their presenting refractive state than typically developing children. Appraisal of refractive error, accommodation, and NVA should be considered in visual assessment of children with ASD.